Development of a comprehensive flourishing intervention to promote mental health using an e-Delphi technique - Gonçalves, Juliane Piasseschi de Bernardin; Braghetta, Camilla Casaletti; Alvarenga, Willyane de Andrade; Gorenstein, Clarice; Lucchetti, Giancarlo; Vallada, Homero (Frontiers in Psychiatry, 2023)
Background: Although observational studies have already shown promising results of flourishing, a broader concept of health based on positive psychology; there is still a gap in the literature regarding studies that combine different topics of flourishing in a single intervention. Objectives: To develop a comprehensive and integrate intervention based on the positive psychology gathering different topics of flourishing to improve mental health outcomes in individuals with depressive symptoms. Methods: The following steps were performed: (1) a comprehensive literature review; (2) the design of a 12-session group intervention based on the values, virtues and topics of flourishing; (3) assessment of the rationale, coherence, and feasibility by a panel of healthcare professionals answering semi-structured questions, and (4) an e-Delphi technique including mental health experts to reach a consensus of at least 80% for each item of the protocol. Results: A total of 25 experts participated in the study, 8 in the panel with semi-structured questions and 17 in the e-Delphi technique. A three-round e-Delphi technique was required to reach consensus for all items. In the first-round, consensus was reached for 86.2% of the items. Remaining items (13.8%) were either excluded or reformulated. In the second round, consensus was not obtained on one item, which was reformulated and approved in the third round. Qualitative analyses of the open questions were performed and suggestions for the protocol were considered. The final version of the intervention was composed of 12 weekly group sessions with 90-minutes each. The topics included in the intervention were physical and mental health, virtues and character strengths, love, gratitude, kindness, volunteering, happiness, social support, family, friends, and community, forgiveness, compassion, resilience, spirituality, purpose and meaning of life, imaging the “best possible future”, and flourishing. Conclusion: The flourishing intervention was successfully developed using an e-Delphi technique. The intervention is ready to be tested in an experimental study to verify its feasibility and effectiveness.